Leveraging single‐pass tangential flow filtration to enable decoupling of upstream and downstream monoclonal antibody processing. (9th February 2018) - Brinkmann, Alex; Elouafiq, Sanaa; Pieracci, John; Westoby, Matthew
Abstract : Decoupling upstream and downstream operations in biopharmaceutical production could enable more flexible manufacturing operations and could allow companies to leverage strategic or financial benefits that would be otherwise unattainable. A decoupling process was developed and scaled up utilizing single‐pass tangential flow filtration for volume reduction, followed by bulk freezing in single‐use bags prior to purification. Single‐pass tangential flow filtration can be used to continuously concentrate harvested cell culture fluid, reducing the volume by 15‐25× with a step yield of >96%. These concentration factors were reproduced with a second product, indicating that the process could be amenable to platform processes. Experimental data indicate that the product tested was stable for at least one year at −40 or −70°C. The concentration of the harvested cell culture fluid—either with or without a subsequent period of frozen storage—had no impact on the product quality attributes that were tested. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:405–411, 2018